Identification of Environmental Issues on the Ecoregion of Volcanic and Fluvio-Volcanic Landform in Badung Regency - Khaerul Amru; Said Fahmi; Mutia Herni Ningrum; Aulia Nur Laksmita; Erwika Dhora Jati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Badung is one of the regencies in Bali province, which is formed by varied landforms with different characteristics. The objective of this study was to identify environmental issues that arise in volcanic and fluvio-volcanic ecoregions in terms of abiotic, biotic, and cultural aspects. The method used to determine the sample in this study was purposive sampling. Meanwhile, the methods used in data collection were surveys and interviews, then analyzed using an ecoregion concept approach and based on resources in the research study area. The research study approach uses a descriptive-analytical approach. The results showed several environmental issues in the research area, mainly caused by human activities, such as agriculture, nature tourism, and fishery. However, several issues were insufficiently coped. Among them, there is an incompatibility in the use of water springs and the accumulation of garbage around the springs in Sibangkaja Village. It might be due to the lack of awareness of the surrounding community towards household waste management. In addition, the handling of river pollution from liquid and solid waste in Sangeh Village has not been managed optimally. Keywords: Badung, ecoregion, environmental issues, fluvio-volcanic landform, volcanic landform